SISTEM PEMBAYARAN SPP MENGGUNAKAN SMS GATEWAY BERBASIS WEB MOBILE DENGAN METODE WEB SCRAPING - Toni Wijanarko Adi Putra; Aldho Dwi Kurniawan (Elkom : Jurnal Elektronika dan Komputer, 2020)
Management of school funds in the form of SPP (Educational Development Donations) at the Kranggan foundation sourced from kindergarten, elementary and junior high schools so far is still managed manually, making it difficult and takes a long time for the Administration to check lists for students who have made payments. Every month. In this study, an SPP payment system was made using an SMS Gateway with the web scraping method. In the development process using the prototype method. The researcher aims to develop a web-based information system that is expected to help manage school payment data for the better. The information system will be equipped with an SMS feature that will be sent to the parents of the students concerned so they can know that the school payment has been made. This SMS feature is also useful for sending reports of late payments or SPP arrears to parents of students whose children are late in paying tuition fees. With this program, students can also make tuition payments in two ways. The first is manually or submitting payment to the TU at the school. The second is by means of money transfer payments through banks.